#TITLE_ALTERNATIVE# - REGAMALELA (NIM : 13413029), DEWI
As technology advances, there is a shift from predominantly physically-demanding tasks to predominantly mentally-demanding tasks. Thus there is a need to regulate (this issue) in order to optimize the mental task load of workers. One of the individual factors that influence mental task load is time orientation. The aim of this research is to identify the influence of time orientation on the perception of task hour needs and mental task load. This research is an experimental laboratory study that involves 92 respondents. The respondents were asked to fill in a Modified Polychoric Attitude Index 3 (MPAI3) questionnaire to differentiate the respondent types between monochronic, neutral, or polycronic. The measuring task load method used was based on performances (accuracy, reaction time, and absolute error), subjective assessment (National Aeronautics and Space Administration Task Load Index and Rating Scale Mental Effort), and assessed objectively using physiology approach (Heart Rate Variability measurement) while the respondents conduct visual memory search and counting task. The result shows that monochronic types are more sensitive in dual task and time pressure conditions. There are significant differences in temporal demand for each type of respondents (monochronic, neutral, and polychronic) to finish the task.